REMEDIASI MISKONSEPSI MATERI GAYA MENGGUNAKAN MODEL LEARNING CYCLE 5E BERBANTUAN MEDIA ANIMASI DI SMP - Hardi Safrianto; Haratua Tiur Maria Silitonga; Erwina Oktavianty (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2022)
This research aimed to determine the effect of 5e learning cycle model in reducing students misconception on force concept in SMP Negeri 1 Jawai Selatan. This research was a pre-experimental with one group pretest-posttest design. This research use intact sample of class VIII C which consist of 28 students. The result of data analysis showed that students misconception before remediation was 78,34% in the all concept of force. Meanwhile, after remediation the misconception decrease by 20,34% to 58% of all concept. The result of McNemar significance test on df = 1 and α = 5% showed x2count > x2table, were equal to 15,91> 3,84. There was a conceptual change on the students significantly. The effect size of this research attain a high result d = 1,242. With the result, 5e learning cycle model assisted animation concept effective to remediated class VIII C student misconception on force concept in SMP Negeri 1 Jawai Selatan.